Model-Based Fault Injection and Diagnostic Validation for AUTOSAR Software Components in Safety-Critical Automotive Systems - Manuel, Calequela Joao Tome; Franco, Jean Cristhiano; Silva, Vinicius Antunes; Santos, Layhon Roberto Rodrigues; Dos Santos, Glaucia Melo; Dias Santos, Max Mauro (Proceedings of the IEEE International Symposium on Industrial Electronics (Online), 2025)
Ensuring the reliability of AUTOSAR software components in safety-critical automotive applications demands rigorous fault injection and diagnostic verification strategies. This paper introduces a systematic methodology for simulating and validating AUTOSAR component behavior within MATLAB/Simulink, utilizing the Diagnostic Event Manager (Dem) to assess fault handling mechanisms. The proposed approach employs Dem Status Override and Dem Status Inject blocks to simulate transient and persistent faults, enabling a comprehensive evaluation of diagnostic responses, fault recovery, and system resilience under abnormal operating conditions. By automating fault injections and validation, the methodology enhances test coverage, improves fault tolerance, and ensures compliance with AUTOSAR diagnostic specifications. Experimental results demonstrate the effectiveness of this framework in identifying vulnerabilities, strengthening component robustness, and streamlining verification processes for embedded automotive software. This work advances model-based fault validation techniques, contributing to the development of safer and more reliable AUTOSAR-compliant embedded systems.